Neuroprotective Efficacy of Asparagus racemosus Root Extract on Hippocampal Neurons in Scopolamine Mouse Model of Alzheimer’s Disease - Jagdish, Prasad; Maheep, Bhatnagar (Asian Journal of Biological and Life Sciences)
Background: Alzheimer’s disease is a one of the prominent cause of senile dementia in the aged people, resulting in mental health deterioration in more than 44 millions of people worldwide. A great majority of currently available medication for neurodegenerative disorders like AD are synthetic in origin and the most of them cause severe side effects. In Ayurveda, an Indian traditional medicinal system, natural products of plant origin has used in since time immorial for treatment of neurodegenerative disorders with the minimum side effects. Asparagus racemosus a household plant is one of them known to possess various biological properties such as antioxidant, anti-apoptotic, adaptogen and Ayuvedic practitioners for neuronal disorders have used for it traditionally. In previous published study from this laboratory, we have shown the nootropic properties of methanolic root extract of Asparagus racemosus using behavioural paradigm. Asparagus racemosus have phytoestrogenic properties with mild estrogenic activities. Estrogen has been reported as potent neuroprotective in various in vivo and clinical studies. In this consequence, the aim of this study was to examine neurorprotective effects of Asparagus racemosus root extraction hippocampal neurons in scopolamine induced Alzheimer’s type dementia in mice. Materials and Methods: The roots of Asparagus racemosus were powdered and extracted in Soxhlet apparatus. The dose of methanolic extract of AR was evaluated for its neuroprotective efficacy against scopolamine induced amnesia in mice. Results and Conclusion: The results of histopathological evaluation showed that methanolic root extract of Asparagus racemosus attenuated the neuronal death in hippocampal CA1, CA3 and DG region induced by scopolamine. These findings indicate that phytoestrogen may serve as potential preventive and therapeutic agent for neurodegenerative disorders.
Keywords: Alzheimer’s disease; Asparagus racemosus; Dementia; in vivo; Neuroprotection